A resistência das mulheres na luta e pela permanência na terra : uma análise no assentamento Maria da Conceição (Orizona/GO) - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The current study tried to understand the countryside as a stuggle territory for land and, with effect, the formative process of women involved in their development due oftheir participation in the achievement and mantenaice of the land. The main goal of the research is to identify and analyse formative spaces for the countryside women in the Settlement Maria da Conceição in Orizona-GO, which have as discussions stake the questions of gender and womenrights focused to to their process of financial and social autonomyand emancipation, in order to (re) define their insertions in the existing job relations in the countryside. The education of women that live in the Settlement Maria da Conceiçãowas investigated beyond the bound aspects to the school education. Whether inherent of their transformations as protagonists of their own reality,in the struggle and contestation of the socioeconomic domination and cultural practices of the capitalism system. The investigation was developed considering their epistemological basis of the historic-dialectical materialism, which involves assume the reality as concrete, synthesis of multiple determinations, therefore, the unity diversity. The methodology consisted inbibliographyc review, observations, interview with the women and photographs of them in their plot of Settlement Maria da Conceição. The obtained results from the empirical research revealed anintense women participation since the ocupation process of land until the the struggle for their permanence. However, the discussions did not guide the gender issues, neither the women rights. It is a family struggle for the basic survival. Although the women have acquired autonomy and leadership in the confrontations, theirspeech even reveal a sexual work division, and the maitenance of the dominant historical gender structure.
Keywords: Mulher; Participação; Assentamento; Processo Formativo; Woman; Participation; Settlement; Formative process; CIENCIAS HUMANAS::SOCIOLOGIA; OUTROS::CIENCIAS SOCIAIS